PENINGKATAN KETERAMPILAN MENULIS SURAT PRIBADI MELALUI PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA KESAPRI (KERTAS SURAT PRIBADI) PADA SISWA KELAS III SD - Vika Irmainsyah; Aulia Tri Lestari; Nida Dhiyaul Auliyah; Rani Setiawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Personal letter writing skills are one of the competencies that elementary school students need to master. However, the results of observations indicate that the personal letter writing skills of third-grade students of SD 1 Wergu Wetan are still low, especially in the aspects of letter structure, letter content, language use, and neatness of writing. This study aims to improve personal letter writing skills through the implementation of the Project Based Learning model assisted by KESAPRI (Personal Letter Paper) media. This study is a Classroom Action Research (CAR) carried out in two cycles using the Kemmis and McTaggart model which includes the stages of planning, action implementation, observation, and reflection. The subjects of the study were 19 third-grade students of SD 1 Wergu Wetan. Data collection techniques used included observation, interviews, tests, and documentation. Data were analyzed qualitatively and quantitatively. The results of the study indicate that the implementation of the Project Based Learning model assisted by KESAPRI media can improve students' personal letter writing skills. The average score of students' writing skills increased from 64 in cycle I to 79.2 in cycle II. The learning completion percentage also increased from 36.84% in cycle I to 63.16% in cycle II. Improvements occurred in the structure of personal letters, content, language use, and neatness of writing. Therefore, the implementation of the Project Based Learning model assisted by KESAPRI media can be an effective learning alternative to improve elementary school students' personal letter writing skills.